Determinants of intention to use e-wallet using TRAM model - Maulidyati Aisyah; Ivana Mutia Eszi (Jurnal Akuntansi dan Auditing Indonesia)
Financial technology also known as Fintech is the result of a combination of financial services and technology. This changes conventional business models to modern ones. One of the Fintech examples in payment category is digital wallet (e-wallet). The purpose of this study is to determine the effects of optimism, innovativeness, discomfort, and insecurity on the perceived ease of use which influence the intention to use e-wallet. The online questionnaire was used to collect the primary data. The respondents in this study were 127 university students in Yogyakarta Province. The data analysis technique used was SEM (Structural Equation Model). The results of this study indicate that optimism and innovativeness have significant effects on perceived ease of use, and perceived ease of use has a significant effect on intention to use e-wallet. Meanwhile, discomfort and insecurity have no effects on perceived ease of use. Meanwhile, the intervening variable, namely perceived ease of use, functions partially.